Morphometric analysis, feeding capacity and proteobacteria wolbachia screening in yellow-assassin bug Cosmolestes picticeps - Muhammad Nasir Dzulhelmi,; Ahmad R. Norhisham,; Mamatnur-Syahirah,; Nursyereen Nasir,; Su Suriyanti,; Madihah Halim,; Wan Nurul Ain Wan Mohd Nor,; Siti Asmah Muslim,; Salmah Yaakop,; Hamidun Bunawan, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The yellow-assassin bug, Cosmolestes picticeps (Hemiptera: Reduviidae) is a generalist predator that has potential use as biological control agent in oil palm agroecosystem. They are known to feed on insect pests like bagworm. To facilitate understanding on the suitability of C. picticeps as an alternative means to manage oil palm pests, and little impact on beneficial insects, this study investigated the morphological variations, feeding capacity and proteobacteria in C. picticeps. To examine the relationships between morphology and feeding capacity of C. picticeps, a total of 90 male and 90 female individuals of C. picticeps collected were measured, and then provided with weevil individuals in captivity. The results showed no significant correlation between the size of C. picticeps with the number of weevil individuals consumed. Meanwhile, the present study also want to determine whether there are proteobacteria Wolbachia sp. in female C. picticeps gut content using Polymerase Chain Reaction (PCR) amplification. The result showed absent of Wolbachia surface protein and Wolbachia citrate synthase coding gene amplification. Based on the present study, more information on the C. picticeps should be assessed as they have the potential as biological control agent to suppress insect pests in agricultural ecosystem.